1998
DOI: 10.1007/s004030050351
|View full text |Cite
|
Sign up to set email alerts
|

Skin mast cell promotion of matrix remodeling in burn wound healing in mice: relevance of chymase

Abstract: Inflammation, granulation, and collagen accumulation, which are observed in the wound healing process, occasionally lead to hypertrophic scarring. Several in vitro reports have suggested that skin mast cells (MCs) and their major protease, chymase, participate in the healing process as well as in fibrotic skin diseases. The present study examined the potential involvement of MCs and MC chymase in the healing of burns in mouse dorsal skin. The size of the burn wounds, density of the capillaries, collagen accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 33 publications
3
52
1
1
Order By: Relevance
“…Mast cells play important roles in multiple physiological and pathological processes, including anaphylaxis and allergic inflammation (2,3), host defense against bacterial (4) and parasitic infection (5), control of endothelin-mediated toxicity (6), regulation of angiogenesis (7), and remodeling of the extracellular matrix (8). Several pathological conditions are associated with accumulation and activation of mast cells in specific organs and tissues, such as bronchi of asthmatic patients (9,10), synovial fluids of patients with rheumatic diseases (11), and certain types of solid tumors in cancer patients (12,13).…”
Section: Ast Cells Are Hemopoietic Cells That Reside In a Varietymentioning
confidence: 99%
“…Mast cells play important roles in multiple physiological and pathological processes, including anaphylaxis and allergic inflammation (2,3), host defense against bacterial (4) and parasitic infection (5), control of endothelin-mediated toxicity (6), regulation of angiogenesis (7), and remodeling of the extracellular matrix (8). Several pathological conditions are associated with accumulation and activation of mast cells in specific organs and tissues, such as bronchi of asthmatic patients (9,10), synovial fluids of patients with rheumatic diseases (11), and certain types of solid tumors in cancer patients (12,13).…”
Section: Ast Cells Are Hemopoietic Cells That Reside In a Varietymentioning
confidence: 99%
“…New investigations are finding that skin mast cells modulate the inflammatory response in healing wounds [6], play a role in neoangiogenesis [7], and may participate in tissue remodeling in the late phase of wound healing [8]. Recent evidence has revealed that skin mast cells and mast cell chymase are important for the formation of granulation tissue and the synthesis of collagen fibers that occur at the edge of the wound in the burnhealing model in mice [9].…”
Section: Introductionmentioning
confidence: 99%
“…Murine skin burn wounds show a rapid increase in mast cell density and chymase activity at the wound edges in the second half of the reepithelializing period (9). Full-thickness skin wounds in mast cell-deficient mice showed normal healing rates but abnormal collagen organization at the wound edges where the preponderance of wound mast cells were found in the late stages of normal healing (49).…”
Section: Discussionmentioning
confidence: 99%
“…Chymase has several actions that could be involved in both normal and pathological wound healing such as angiotensin II formation (4), degradation of extracellular matrix (5), and activation of matrix metalloproteinases (6) and cytokines, including TGF-␤1 (7) and antibacterial peptides (8). The presence of mast cell chymase has been noted in skin wounds (9), although it is not clear that the enzyme can diffuse to the zone of reepithelialization (10). A few studies have reported non-mast cell sources of chymase.…”
mentioning
confidence: 99%